Remittance and Economic Development of Nepal (Patan Pragya, 2019)
Nepal is one of the least developed but high remittances recipient countries in the world. Nepal received remittance from US$ 8.1 billion in 2016 and it is ranked 23rd among the remittance receiving countries in the world. Remittance income is one of the major sources of capital formation in the context of Nepal. It is directly related with the labour migration in a country which in return enhances foreign employment. Remittances have become a major contributing factor to increasing household income as well as country’s GDP. About 30 percent of Nepal’s GDP comes in the form of remittance money which is sent home by Nepalese working abroad and it helps to reduce country’s poverty rate. Poverty reduction took place in Nepal from 42 percent (1995/96) to 25.2 percent (2010/11). Nepal’s remittance recipients reached 31.5 percent GDP in 2015. The total amount of remittance in the country is 259 billion and among which 20 percent is internal sources, 11 percent from India and 69 percent from Gulf countries. Remittance received by the households is mainly used for daily consumption (79 percent) and remaining other purposes. Moreover, Nepal’s economic status mostly depends on remittance received which is therefore migration driven economy.